Adaptive sampling with mobile WSN simultaneous robot localisation and mapping of paramagnetic spatio-temporal fields - Sreenath, Koushil; Mysorewala, Muhammad F.; Popa, Dan O.; Lewis, Frank L. (The Institution of Engineering and Technology, 2011)
The book is organized into three parts: preliminaries, single-robot adaptive sampling and multi-resource strategies.